2007
DOI: 10.1093/carcin/bgl128
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrative stress caused by subcutaneous implantation of a foreign body accelerates sarcoma development in Trp53+/- mice

Abstract: Chronic inflammation is a recognized risk factor for human cancer at various sites because of persistent oxidative and nitrative tissue damage. Trp53+/- mice show the predisposition to tumor development, such as sarcomas and lymphomas, compared with Trp53+/+ mice. We investigated the effects of chronic inflammation, especially oxidative and nitrative stress, induced by subcutaneous implantation of a plastic plate (10 x 5 x 1 mm) as a foreign body on tumorigenesis in Trp53+/- and Trp53+/+ mice. The plastic plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…(37) 8-Nitroguanine is also detected in the colonic gland epithelial cells of a mouse model of inflammatory bowel disease (59) and in soft tissue sarcoma cells in mice after subcutaneous implantation of a plastic plate. (60) These studies indicate that 8-nitroguanine is a potential mutagenic DNA lesion generated during inflammation. Thus, 8-nitroguanine may be used as a predictive marker directly evaluating the risk of inflammation-related carcinogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…(37) 8-Nitroguanine is also detected in the colonic gland epithelial cells of a mouse model of inflammatory bowel disease (59) and in soft tissue sarcoma cells in mice after subcutaneous implantation of a plastic plate. (60) These studies indicate that 8-nitroguanine is a potential mutagenic DNA lesion generated during inflammation. Thus, 8-nitroguanine may be used as a predictive marker directly evaluating the risk of inflammation-related carcinogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…10 Tazawa et al identified some genes possibly responsible for the development of foreign-body-induced sarcomas. 71 They found that in 79% heterozygous p53-deficient (Trp53 1/2 ) mice with only 1 functional allele in the p53 gene developed spontaneous sarcomas after plastic plate implantation, whereas only 10% of mice with wild-type p53 developed sarcomas. They further demonstrated that the arising tumors have lost the remaining wild-type p53 allele, meaning complete loss of p53 function; this appears to be the underlying molecular mechanism during the development of sarcomas.…”
Section: Foreign-body-induced Experimental Carcinogenesismentioning
confidence: 99%
“…p53 allele is inactivated by an increase of inflammation-mediated RNS. 71 Association between RNS and p53 mutations is evidenced in inflamed lesions of the colon with ulcerative colitis, 72 stomach, 73 brain 74 and breast. 75 The susceptibility to foreign-body-related carcinogenesis does exist across species, and in strain-and gender-dependent manner.…”
Section: Foreign-body-induced Experimental Carcinogenesismentioning
confidence: 99%
“…Tazawa et al observed a high incidence of spontaneous autologous tumors in p53 genedisrupted mice after subcutaneous implantation of a small piece of plastic plate [67]. The plastic plate was recognized as foreign body in the mice, and the foreign body-induced inflammation caused the tumor at the implantation site.…”
Section: Genetic Mechanisms In Inflammation-induced Carcinogenesismentioning
confidence: 99%